Determinants of Oil Futures Prices - Abraham, Rebecca; Harrington, Charles (Scientific Research, 2016)
This study is directed at predicting the determinants of oil futures prices. We evaluate commodity pricing with oil occupying a special position due to highly inelastic demand. Given the sudden fall in oil prices, there is theoretical and practical interest in identifying the determinants of falling oil prices. While the popular press dwells on oversupply in production as the principal determinant of price declines, we examine additional predictors including call option sales and put option purchases along with the Canadian dollar-US dollar exchange rate and news of future oil prices. Intraday call and put options on NYMEX oil futures were examined. Call and put option prices of 1 - 7 month-maturities, along with exchange rates, the supply of oil and news of oil prices were regressed on oil futures prices. A trading strategy was tested based on the thesis that in a period of price declines, options traders seek to profit by selling call options and purchasing put options. While oversupply of oil was the most important determinant of oil prices, trader speculation through put buying and call selling exacerbated the decline in oil prices. Call and put option prices explained oil futures prices for options of 1 - 4 month maturities. The supply of oil was significant in predicting oil futures prices in all future time periods. This was followed by the Canadian dollar-US dollar exchange rate which was significant in predicting oil prices 1, 2, 3 and 6 months into the future. Finally, news of forthcoming events affecting oil prices predicted oil futures prices 3, 4, 5, 6 and 7 months in advance.
Keywords: Oil Futures; Options; Negative Volume; Price Declines